Anambas Island Coastal Empowerment Strategy For Development Facilities And Infrastructure: Strategi Pemberdayaan Masyarakat Pesisir Kepulauan Anambas Dalam Pengembangan - Fitri Yeni, Ulfa Ayu; Hambali (Progress In Social Development, 2022)
ABSTRACT: Development in the community has a sufficient process through many stages that aim to achieve community welfare. The provision of access to electric lighting and access to clean water, which are fundamental interests in supporting community activities, is a problem that is often encountered in certain areas, such as in Belibak Village which is a village located in the Palmatak District, Anambas Islands Regency, Riau Islands Province. Coastal areas and islands inhabited by fishing communities are often faced with limited access to basic needs, uneven development felt by the community, several factors that cause uneven development in archipelagic areas, one of which is the geographical location of an area that makes it difficult to enter development. Like the people of Belibak Village, who feel the impact of the geographical location, which makes Belibak Village have serious problems in the provision of clean water and the provision of electricity networks. ABSTRAK: Pembangunan pada masyarakat memiliki proses yang cukup melalui banyak tahapan yang bertujuan untuk tercapainya kesejahteraan masyarakat. Penyediaan akses penerangan listrik dan akses air bersih yang merupakan kepentingan mendasar dalam penyokong aktivitas masyarakat menjadi permasalahan yang sering dijumpai pada wilayah-wilayah tertentu seperti halnya di Desa Belibak yang merupakan desa yang terletak di wilayah Kecamatan Palmatak, Kabupaten Kepulauan Anambas, Provinsi Kepulauan Riau. Wilayah pesisir dan kepulauan yang dihuni oleh masyarakat nelayan sering dihadapkan dengan keterbatasan akses untuk pemenuhan kebutuhan dasar, tidak meratanya pembangunan yang dirasakan oleh masyarakat beberapa faktor yang menyebabkan tidak meratanya pembangunan pada daerah kepulauan salah satunya adalah faktor letak geografis sebuah wilayah yang menyulitkan masuknya pembangunan. Seperti halnya masyarakat Desa Belibak yang merasakan dampak dari letak geografis tersebut yang membuat Desa Belibak memiliki permasalahan serius dalam pengadaan air bersih dan pengadaan jaringan listrik.